A study on the optimization nodes arrangement in UWB localization. (15th October 2020) - Wang, Shijia; Wang, Shibo; Liu, Wanli; Tian, Ye
Highlights: The arrangement of reference nodes has an influence on the localization accuracy of target node. The ultra wideband ranging error model is built under the non-line-of-sight environment. An optimal arrangement searching-method fusing the ranging error is proposed. Abstract: Because of space limitations in a longwall mining face, ultra wideband (UWB) localization has to be conducted in a non-line-of-sight (NLOS) environment. In order to improve the UWB localization accuracy, a search method for the optimal arrangement of the reference nodes based on genetic algorithm (GA) is proposed. This search method fuses GA with a ranging error model of UWB in NLOS environment which was built by authors previously. The optimal arrangement of UWB nodes in the longwall mining face is obtained using numerical simulation and experiments are conducted for verification. The mean errors of the target node positions are less than 16 cm.